1988
DOI: 10.2337/diacare.11.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Topical Hyperbaric Oxygen for Treatment of Diabetic Foot Ulcers

Abstract: The effect of 2 wk of topical hyperbaric oxygen (THO) treatment on the healing of diabetic foot ulcers without associated gangrene was evaluated in a prospective, controlled, and randomized manner in 28 patients. There were 12 patients in the THO group (group 1) and 16 in the control group (group 2). Clinical management of the two patient groups was similar except for THO treatment in the group 1 patients. Clinical parameters, including age, sex, baseline fasting serum glucose levels, duration of diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 13 publications
0
63
0
Order By: Relevance
“…The application of positive pressure oxygen to manage open wounds has been studied extensively and has demonstrated promising clinical results [20][21][22][23][24][25][26][27][28]. The systemic complications associated with the use of a full-body hyperbaric chamber have been overcome by the application of topical wound pure oxygen at an appropriate cycled pressure to only the specific wound site.…”
Section: Topical Wound Oxygenmentioning
confidence: 99%
“…The application of positive pressure oxygen to manage open wounds has been studied extensively and has demonstrated promising clinical results [20][21][22][23][24][25][26][27][28]. The systemic complications associated with the use of a full-body hyperbaric chamber have been overcome by the application of topical wound pure oxygen at an appropriate cycled pressure to only the specific wound site.…”
Section: Topical Wound Oxygenmentioning
confidence: 99%
“…39 Leslie et al, in a randomized controlled study showed that patients receiving TOT (n 5 12) displayed a longer healing duration as opposed to patients who received standard care alone (n 5 16). 28 In this study TOT was administered to patients with DFUs in two daily 90-min sessions through a leg chamber that provided humidified 100% oxygen at pressures cycled between 0 and 30 mm Hg (i.e., up to 1.04 atm abs) every 20 s. At day 14 wound size was significantly reduced in all patients, irrespective of which group they were assigned to (p . 0, 05).…”
Section: Con: Topical Oxygen For Wounds Is Not Effectivementioning
confidence: 98%
“…TOT opponents frequently cite a randomized controlled study conducted by Leslie et al as a clear evidence that TOT is not effective. 28 This study, however, has serious methodological flaws. The most significant of these is that, although TOT does not penetrate to bone, a substantial rate of patients with findings suggestive of osteomyelitis were included in the study [6 (50%) of the patients receiving TOT had abnormal bone scans or x rays and above 70 mm/h sedimentation rate].…”
Section: Introductionmentioning
confidence: 99%
“…One was randomized and reported no apparent reduction in the cross-sectional area of ulcers at either 7 or 14 days [33]. The other was only partially randomized but reported an apparent benefit at 4 weeks [34].…”
Section: Topical Hbomentioning
confidence: 99%